Pengaruh Kredibilitas Endorse dan Keterlibatan Sosial Media Instagram Terhadap Keputusan Pembelian dengan Mediasi Minat Beli - Reyna Yunita; Moh Rifqi Khairul Umam (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research was conducted because there was an increase in purchases of Le Minerale products in 2024 where in that year Le Minerale collaborated with the endorse of its choice so that the credibility of Endorse influenced purchasing decisions for consumers. This study aims to explain the significant effect obtained from the results of testing the Endorse Credibility variable data on buying interest mediated by the presence of Instagram Social Media Involvement. The Stumulus-Organism-Response (SOR) model is used to be able to explain the relationship between variables in this study. Quantitative methodology was used in this study by distributing questionnaires to 120 respondents. Sampling technique used is non probability sampling with purposive sampling technique and analyzed using SmartPLS 3.0 software.